A tributação do PIS/PASEP e da COFINS sobre os combustíveis: uma análise dos coeficientes de redução de alíquota à luz dos princípios constitucionais tributários da legalidade e da anterioridade - Fernandes, Távisson Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
In the presente work we proposed to study the reduction coefficients of tax rate, legal institute provided by the special arrangements for apuration and payment of PIS/PASEP and also of COFINS on fuels. The purpose of this monography is to analyze the legal nature of the reduction coefficients of tax rate, your observance and conformity (or not) to the tax constitutional principles of legality and anteriority, measure if the Decree n.º 9.101/17 directly infringes the Federal Constitution or if that consists in a reflexive violation and describe the legal provisions that support the institution of the reduction coefficients of tax rate. For the approach this issue, we use the deductive method, about the procedure, we adopt the typological method, and finally, about the technical of work, we found support in the indirect documentation. We conclude the reduction coefficients of tax rate are a tax incentive modality, as a differential treatment of a tax nature, institute inserted into the inductive tax rules gender. We also infer the indirect increase of taxes, by the reduction or extinction of the reduction coefficients of tax rate, occurred with the edition of the Decree n.º 9.101/17, infringes the tax legal order, because that is contrary to the tax constitutional principles of legality and anteriority.
Artigo Acadêmico
Keywords: Coeficientes de redução de alíquota; Anterioridade tributária; Legalidade tributária; Reduction coefficients of tax rate; Tax anteriority; Tax legality; CIENCIAS SOCIAIS APLICADAS::DIREITO